Criminal Legal Protection of Property in Russia in the Conditions of Development of Property Relations - Vasilievich Groshev, Aleksandr; Georgievich Saprunov, Aleksandr; Vladimirovich Shulga, Andrey; Rakhimmulovich Galiakbarov, Romen; Aleksandrovich Tushev, Aleksandr (International Journal of Engineering and Technology, 2018)
The main purpose of the work is to prove that the subject of thefts and other crimes against proprietorship, which is property, should be interpreted in a broad sense â€“ not only as choses, but also as other property, including property rights. The method of achieving this goal is to justify the fact that in the conditions of building an information society and developing market economy, the field of property turnover is expanding. Economic relations increasingly include both material benefits â€“ choses - and other property that does not have any physical parameters of a traditional chose, being incorporeal, intangible, having the information nature. This tendency is undoubtedly taken into account by the criminal environment, which increasingly often commits crimes aimed at unlawful acquisition of this incorporeal property.Therefore, it is required to strengthen the legal protection of nonmaterial property by criminal legal means, recognizing the thefts of both choses and material goods as the subjects of crimes against property. As a result of unlawful acquisition of these goods, property damage is also caused to their owners. The recognition of property rights as the subject of theft determines the novelty of this article.Â Â